2010
DOI: 10.1021/np900827a
|View full text |Cite
|
Sign up to set email alerts
|

Humulane and Germacrane Sesquiterpenes from Ferula lycia

Abstract: Five new juniferol esters (1-5), along with six known humulane derivatives (6-11), were isolated from the roots of Ferula lycia, an endemic Turkish species. The fruits of the same species were also investigated and led to the isolation of these same compounds, as well as two known germacrane esters (12 and 13). All isolated sesquiterpenes were assayed for cytotoxicity against two tyrosine kinase inhibitor-resistant cell lines, K562R and DA1-3b/M2(BCR-ABL). The two most active compounds, juniferinin (7) and 6-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…persica and F. halophila, as well as the hexane extract of F. elaeochytris, were assigned to be more active than methanolic extracts of the plants [36][37][38]. In addition, the acetylcholinesterase inhibitory activities of coumarin derivatives from F. gummosa and F. asafoetida species were determined, previously [30][31][32][33][34][35][36][37][38][39][40][41]. In the current study, the chloroform extracts of F. caspica and F. halophila that could be expected to contain some coumarin derivatives weren't found to be as active as methanol extracts of the plants compared to standard donepezil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…persica and F. halophila, as well as the hexane extract of F. elaeochytris, were assigned to be more active than methanolic extracts of the plants [36][37][38]. In addition, the acetylcholinesterase inhibitory activities of coumarin derivatives from F. gummosa and F. asafoetida species were determined, previously [30][31][32][33][34][35][36][37][38][39][40][41]. In the current study, the chloroform extracts of F. caspica and F. halophila that could be expected to contain some coumarin derivatives weren't found to be as active as methanol extracts of the plants compared to standard donepezil.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, sesquiterpene and coumarin derivatives were isolated from apolar extracts of Ferula species [29][30][31][32]. Studies on the polar metabolites are unfortunately limited.…”
Section: Lc-ms Analysis Of Phenolic Compoundsmentioning
confidence: 99%
“…[27], F. orientalis [28], F. rigidula [29], F. haussknechtii [30] and F. lycia Boiss. [31] from Subgenus Peucedanoides yield mainly daucane, apiene and germacrane sesquiterpene esters. Because of the presence of multiple chiral centers and variety of structural features such as mono-, di-, tricylic skeletons that vastly enhance their structural diversity, utilization of the sesquiterpenoid compounds as chemotaxonomic markers provide an unparalleled advantage over the use of classical phenolic chemotaxonomic markers such as flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…4 Monoterpenes, sesquiterpenes (especially daucanes, humulanes, and guaianes type sesquiterpene esters, sesquiterpene lactones), coumarins were found to be the main constituents of the Ferula genus by phytochemical studies. [5][6][7][8] Phenylpropanoid, sulphur containing derivates, triterpenes and their glycosides were also reported. [9][10][11] Recent pharmacological research has demonstrated that different extracts of Ferula species contain sesquiterpene derivatives have in particular proven to be cytotoxic on several cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%